30 кэВ энергитэй нейтроноор явагдах (n,gamma) урвалын дундаж огтлолын систематик анализ - Г, Хүүхэнхүү; А, Дулмаа (Scientific transaction of the National University of Mongolia. Physics, 2022)
The dependence of experimental (n, gamma) cross sections fot 30 keV neutron on a target-nucleus neutron number, neutron binding energy and level density parameters are analyzed using statistical model of nuclear reactions.